Prison Culture as Rape Supportive: Applying Importation and Deprivation Models to Examine Inmate Beliefs - Fowler, Shannon K. (Journal of interpersonal violence, 2022)
While research examining sexual violence in prison has increased over the past 15 years, relatively scant attention has been paid to rape supportive beliefs and the factors influencing inmate adherence to these beliefs. Given the demonstrated role from studies outside the prison context that rape supportive beliefs have on sexual violence, important parallels can be drawn from studying the inmate population. Importation and deprivation models have been used to explain how inmates adapt to prison life?whether attitudes and behaviors are imported from their lives outside prison or are developed in prison due to the conditions of incarceration. Using a sample of male and female inmates (n = 875) from a large state prison system in the southern United States, the researchers explored the degree to which inmate rape supportive beliefs (IRSB) were influenced by variables indicative of importation or deprivation models of prison adaption. Findings revealed greater support for importation variables among both male and female inmates. With some variation, measures such as gender, age, ethnicity, and education were significant in explaining IRSB, similar to findings of studies on rape supportive beliefs among noninmate samples. Because these beliefs can manifest in problematic attitudes and behaviors among inmates, such as prison sexual violence and the underreporting of such violence, it is important that correctional administrators understand this relationship and take steps to lessen IRSB. Since IRSB largely correlate with factors unrelated to conditions of confinement, efforts to educate and sensitize inmates to prison sexual violence can replicate best practices based on populations outside of prisons.